ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN PSAK NOMOR 409 DALAM PENYUSUNAN LAPORAN KEUANGAN PADA BAZNAS KABUPATEN SAROLANGUN JAMBI - Herlina; Usdeldi (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to analyze the implementation of PSAK No. 409 at the Sarolangun Regency BAZNAS. Qualitative methods were used, including interviews and documentation. The study found that BAZNAS is not yet fully compliant with PSAK 409. Its financial reports are limited to fund receipts and disbursements. Furthermore, the publication of financial reports has not been consistently conducted, thus hindering the principle of transparency. Challenges faced by BAZNAS in Sarolangun Regency include irregular financial report audits, limited human resources, and inconsistent financial report publication. Recommendations for BAZNAS include preparing more comprehensive financial reports in accordance with PSAK 409, including cash flow statements, changes in assets under management, and notes to the financial statements.